The prevalence of childhood psychopathology in Turkey: a cross-sectional multicenter nationwide study (EPICPAT-T) - ARMAN, AYŞE; PERDAHLI FİŞ, NEŞE (TAYLOR & FRANCIS LTD, 2022)
Aim: The aim of this study was to determine the prevalence of childhood psychopathologies in Turkey. Method: A nation-wide, randomly selected, representative population of 5830 children (6-13 years-old) enrolled as a 2nd,3rd or 4th grade student in 30 cities were evaluated for presence of a psychiatric or mental disorder by a Sociodemographic Form, Kiddie Schedule for Affective Disorders and Schizophrenia for School Age Children-Present and Lifetime Version (K-SADS-PL), and DSM-IV-Based Screening Scale for Disruptive Behavior Disorders in Children and Adolescents scales. Impairment criterion was assessed via a 3 point-Likert scale by the parent and the teacher independently. Results: Overall prevalence of any psychopathology was 37.6% without impairment criterion, and 17.1% with impairment criterion. Attention-deficit hyperactivity disorder was the most frequent diagnosis, followed by anxiety (19.5% and 16.7% without impairment, 12.4% and 5.3% with impairment, respectively). Lower education level and presence of a physical or psychiatric problem of the parents were independent predictors of any psychopathology of the offspring. Conclusion: This is the largest and most comprehensive epidemiological study to determine the prevalence of psychopathologies in children and adolescents in Turkey. Our results partly higher than, and partly comparable to previous national and international studies. It also contributes to the literature by determining the independent predictors of psychopathologies in this age group.
Keywords: Psychiatric; mental; psychopathology; prevalence; epidemiology; Turkey; ATTENTION-DEFICIT/HYPERACTIVITY DISORDER; PSYCHIATRIC-DISORDERS; EMOTIONAL-PROBLEMS; MENTAL-DISORDERS; TURKISH CHILDREN; SCHOOL-CHILDREN; ADOLESCENTS; HEALTH; IMPAIRMENT; COMMUNITY